2002
DOI: 10.1254/jjp.89.349
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine Receptors, Especially the 5-HT4 Receptor, in Guinea Pig Urinary Bladder

Abstract: ABSTRACT-The function of 5-hydroxytryptamine (5-HT) receptors, especially the 5-HT4 receptor, in the urinary bladder were examined in preparations isolated from the guinea pig by in vitro receptor autoradiography and determinations of mechanical activity and acetylcholine (ACh) release. Specific The bladder functions are controlled by the integration of excitatory, inhibitory and sensory nerve activity in the spinal cord, pons and forebrain; and 5-hydroxytryptamine (5-HT) has been identified as an inhibitory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In the bladder, contractile responses to serotonin are mediated by the 5-HT 2 receptor [Kim et al, 2002;Yoshida et al, 2002]. Interestingly, the 5-HT 2A receptor has been shown to concentrate in caveolae of circular and longitudinal smooth muscle of rat intestine [Fiorica-Howells et al, 2002] and to associate with caveolin-1 in glioma cells [Bhatnagar et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…In the bladder, contractile responses to serotonin are mediated by the 5-HT 2 receptor [Kim et al, 2002;Yoshida et al, 2002]. Interestingly, the 5-HT 2A receptor has been shown to concentrate in caveolae of circular and longitudinal smooth muscle of rat intestine [Fiorica-Howells et al, 2002] and to associate with caveolin-1 in glioma cells [Bhatnagar et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…In the isolated guinea pig bladder, it has been reported that 5-HT 2A and 5-HT 4 receptors are involved in enhancing purinergic transmission and that the 5-HT 3 receptor is involved in enhancing cholinergic transmission (Messori et al, 1995). Yoshida et al (2002) studied the 5-HT receptors in guinea pig urinary bladder preparations by in vitro receptor autoradiography and determinations of mechanical activity and acetylcholine release. Specific binding sites were detected evenly throughout the urinary bladder.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…Several in vitro studies have shown that the contractile effect of mammalian detrusor in response to 5-HT exposure is mediated by activation of 5-HT 2 , 5-HT 3 , and 5-HT 4 receptors (Yoshida et al, 2002). In the human detrusor, 5-HT potentiates the neurogenic contractions by activating the 5-HT 4 receptor type .…”
mentioning
confidence: 99%